Students' Perceptions on Using Extending Concept Through Language Activities to Improve Students' Reading Comprehension Skill - Lutviana, Rizky; Rafika Sinta Nurrona; Maria Purnawati; Novi Sriwulandari (E-Link Journal, 2024)
The pupose of this study was to understand students' perceptions about potential and benefits of improving Extending Concept Through Language Activities (ECOLA) method as a tool for improving students' reading comprehension skill. This study used a descriptive qualitative with the subjects of 19 students of the 10th grade of Vocational High School of SMK Islam Gondanglegi. Data collection was carried out through questionnaire based on likert scale and interview. In collecting data, questionnaire were made to collect information on respondents’ perceptions of the ECOLA method and its impact on their reading comprehension skills, while the interview were made to obtain further information regarding students perceptions about using the ECOLA method. Based on the analysis of the results, researcher concluded that the ECOLA method generally has positive acceptance for improving reading comprehension skills. This is evident from the results of the questionnaire which shows the high motivation and enthusiasm of the participants. 65% of respondents agreed that this method had improved their reading comprehension skills. Additionally, 80% of respondents agreed that ECOLA helped them understand reading material better. Likewise, in interviews, participants expressed appreciation and satisfaction with ECOLA's approach, which includes interactive discussions and enhanced learning experiences.